Determining the Criteria Identifying Teacher Performance Through Multiple Indicators - Sayin, Sanem Dilbaz; Arslan, Hasan (European Scientific Journal, ESJ, 2017)
This study focused on determining the criteria for the assessment of teachers’ performance. It aimed to determine ‘Teachers’ Performance Assessment Scale’ through the opinions of teachers, administrators, and students. Semi-structured interviews were conducted to gather the opinions of the participants. Four education-specialists took part in the interviews and analysis of the data. The data were analyzed by means of factor analysis and varimax method was used to reduce the items and group the related ones. According to the results, ‘Teacher Performance Assessment Scale’ included 39-item and 6 sub-dimensions. Besides, self-evaluation and long term observation of multiple indicators were found to be the most appropriate ways to evaluate teachers’ performance.